A stretchable and sensitive light-emitting fabric. Issue 17 (13th April 2017) - Zhang, Zhitao; Shi, Xiang; Lou, Huiqing; Xu, Yifan; Zhang, Jing; Li, Yiming; Cheng, Xunliang; Peng, Huisheng
Abstract : A stretchable and sensitive light-emitting fabric is developed, which can be stretched as high as 100%. Abstract : A novel type of lightweight and stretchable light-emitting fabric is developed with the highest brightness that is above 70 cd m −2 . The brightness of the stretchable light-emitting fabric can be maintained at 98.5% even after stretching for 100 cycles at a strain of 100% with a stretching speed of 10% strain per s. This stretchable light-emitting fabric is further integrated with different colors of light-emitting modules for display. It is also able to detect external stimuli such as pressure, accompanying this detection with a visual feedback.